Discovery of internet topology knowledge and its applications - ZHANG Guo-qing (Tongxin xuebao)
At first the definition of network structure and the differences between analysis method to network structure and those in the traditional disciplines were introduced.Then the Internet was taken as example to review main properties in the internet topologies,point out some widely existing misunderstandings,and present some applications which used topology knowledge of the internet.Finally,from the perspectives of both practical and academic development,the significance of new findings in the network topologies was highlighted.